Geotextile testing and the design engineer : - Fluet, Joseph E.; ASTM. Committe D-35 on Geotextiles, Geomembranes and Related Products; ASTM Symposium on Geotextiles Testing and the Design Engineer (1985 : Los Angeles, Calif.) (Philadelphia, Pa : ASTM, 1987)
09